Modeling Motorcyclists Aggressive Driving Behavior Using Computational and Statistical Analysis of Real-Time Driving Data to Improve Road Safety and Reduce Accidents - Abdulwahid S.N.; Mahmoud M.A.; Ibrahim N.; Zaidan B.B.; Ameen H.A. (MDPI, 2023)
accident prevention; aggression; cycle transport; modeling; real time; road traffic; statistical analysis; transportation safety; accident; aggression; aggressive driving; Article; data analysis; decision tree; driving ability; global positioning system; human; machine learning; motorcycle; motorcyclist; road safety; support vector machine; car driving; prevention and control; safety; traffic accident; Accidents, Traffic; Aggressive Driving; Automobile Driving; Humans; Motorcycles; Safety